(E)-3-(4-Decyloxyphenyl)-1-(2-hydroxyphenyl)prop-2-en-1-one - Zainab, Ngaini; Norashikin Irdawaty, Abd Rahman; Hasnain, Hussain; Ibrahim, Abdul Razak; Fun, Hoong-Kun (PubMed, 2009)
In the title compound, C 25 H 32 O 3 , the enone group is in an s–cis conﬁguration. The dihedral angle between the benzene rings is 8.84 (7). An intramolecular O—HO interaction between the keto and hydroxy groups forms an S(6) ring motif. Intermolecular C—HO interactions link the molecules into supramolecular chains along the caxis which are subsequently stacked down the baxis; the crystal structure is further consolidated by C—Hinteractions.